EFFECT OF "VETOM 21.77" PREPARATION ON SERUM BIOCHEMICAL PATTERN IN MICE - E. R. Rafikova (Ветеринария сегодня)
It is known that predatory Hyphomycetes fungi play an important role in measures taken for helminthic infestation prevention. There is little evidence on properties of compounds contained in predatory fungi and their effect on animals. Results of tests of "Vetom 21.77", new microbiological preparation based on Duddingtonia flagrans, for its effect on serum biochemical pattern of laboratory mice are presented. The preparation was administered to the animals at the dose of 2, 5, 50 and 300 µl/kg of body weight. The animals were examined for tested parameters prior and 2 and 7 days after daily administration of the preparation. The parameters remained within the normal physiological limits in all test group as well as in control group not given the preparation. The test results indicated safety of the said microbiological preparation. Significant increase in total protein and albumin contents was recorded in mice given the maximum dose of the preparation as compared with those of control group.